Comparative effectiveness and costs of generic and brand-name gabapentin and venlafaxine in patients with neuropathic pain or generalized anxiety disorder in Spain - Sicras-Mainar A; Rejas-Gutiérrez J; Navarro-Artieda R (Dove Medical Press, 2015)
Antoni Sicras-Mainar,1 Javier Rejas-Gutiérrez,2 Ruth Navarro-Artieda3 1Planning Directorate, Badalona Serveis Assistencials SA, Badalona, Barcelona, Spain; 2Department of Health Economics and Outcomes Research, Pfizer SLU, Alcobendas, Madrid, Spain; 3Medical Documentation, Hospital Germans Trias i Pujol, Badalona, Barcelona, Spain Objective: To explore adherence/persistence with generic gabapentin/venlafaxine versus brand-name gabapentin/venlafaxine (Neurontin®/Vandral®) in peripheral neuropathic pain (pNP) or generalized anxiety disorder (GAD), respectively, and whether it is translated into different costs and patient outcomes in routine medical practice. Methods: A retrospective, new-user cohort study was designed. Electronic medical records (EMR) of patients included in the health plan of Badalona Serveis Assistencials SA, Barcelona, Spain were exhaustively extracted for analysis. Participants were beneficiaries aged 18+ years, followed between 2008 and 2012, with a pNP/GAD International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code, who initiated treatment with generic or brand-name gabapentin or venlafaxine. Assessments included 1-year treatment persistence and adherence (medication possession ratio), health care costs, and reduction in severity of pain and anxiety symptoms. Results: A total of 2,210 EMR were analyzed; 1,369 on gabapentin (brand 400; generic 969) and 841 on venlafaxine (brand 370 and generic 471). Brand-name gabapentin and venlafaxine were both significantly associated with longer persistence than generic: 7.3 versus 6.3 months, P<0.001; and 8.8 versus 8.1 months, P<0.05, respectively. Brand-name was associated with higher adherence: 86.5% versus 81.3%, P<0.001; and 82.1% versus 79.0%, P<0.05, respectively. Adjusted average costs were higher with generic compared with brand: €1,277 versus €1,057 (difference of €220 per patient; P<0.001) for gabapentin; and €1,110 versus €928 (difference of €182 per patient; P=0.020) for venlafaxine, both because of more use of medical visits and concomitant medication. Compared with generic, brand-name was associated with higher reduction in pain (7.8%; P<0.001) and anxiety (13.2%; P<0.001). Conclusion: Patients initiating brand-name gabapentin or venlafaxine were more likely to adhere and persist on treatment of pNP or GAD, have lower health care costs, and show further reduction of pain and anxiety symptoms than with generic drugs in routine medical practice. Keywords: brand medicinal products, generic medicinal products, adherence, persistence, use of resources, costs, outcomes